2005
DOI: 10.1103/physrevlett.95.176801
|View full text |Cite
|
Sign up to set email alerts
|

Surface Trapped Excess Electrons on Ice

Abstract: Local trapping of excess electrons at the surface of solid water systems has recently been observed in large water clusters and at the ice/vacuum interface. The existence of stable surface-bound states for the excess electron may have important implications in atmospheric chemistry, electrochemistry, and radiation physics. By means of first-principles molecular dynamics we find that excess electrons induce a structural reconstruction of the ice surface on a time scale of a fraction of a picosecond. The surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 34 publications
5
71
0
Order By: Relevance
“…Earlier femtosecond time-resolved spectroscopic studies by Wolf's group [64] and Petek's group [65] on thin amorphous ice films (a few monolayers) on a metal or insulator substrate showed lifetimes of less than 1 ps for the presolvated electrons. By first-principles molecular dynamics simulations of the ice surface at the temperatures close to those found in PSCs (150-200 K), Baletto et al [63] found very stable surface-bound states for trapping electron at the ice surface due to the structural rearrangement induced by an excess electron. They proposed that the surface molecular rearrangement leads to an increase of the number of dangling OH bonds pointing towards the vacuum and to the formation of an electrostatic barrier preventing the decay of the electron into the bulk solvated state [63].…”
Section: More Justification Of the Cosmic-ray-driven-electron-reacmentioning
confidence: 91%
See 2 more Smart Citations
“…Earlier femtosecond time-resolved spectroscopic studies by Wolf's group [64] and Petek's group [65] on thin amorphous ice films (a few monolayers) on a metal or insulator substrate showed lifetimes of less than 1 ps for the presolvated electrons. By first-principles molecular dynamics simulations of the ice surface at the temperatures close to those found in PSCs (150-200 K), Baletto et al [63] found very stable surface-bound states for trapping electron at the ice surface due to the structural rearrangement induced by an excess electron. They proposed that the surface molecular rearrangement leads to an increase of the number of dangling OH bonds pointing towards the vacuum and to the formation of an electrostatic barrier preventing the decay of the electron into the bulk solvated state [63].…”
Section: More Justification Of the Cosmic-ray-driven-electron-reacmentioning
confidence: 91%
“…By first-principles molecular dynamics simulations of the ice surface at the temperatures close to those found in PSCs (150-200 K), Baletto et al [63] found very stable surface-bound states for trapping electron at the ice surface due to the structural rearrangement induced by an excess electron. They proposed that the surface molecular rearrangement leads to an increase of the number of dangling OH bonds pointing towards the vacuum and to the formation of an electrostatic barrier preventing the decay of the electron into the bulk solvated state [63]. Most recently, interesting results were reported by Wolf, Bovensiepen and co-…”
Section: More Justification Of the Cosmic-ray-driven-electron-reacmentioning
confidence: 91%
See 1 more Smart Citation
“…The BLYP exchange-correlation energy functional was used for the neutral structures. In the presence of the excess electron an additional approximate correction for the self-interaction was employed as described and tested in ref 10. The approach we pursue here allows for an interaction of the excess electron with the valence electrons of individual water molecules and hence gives a realistic account of the decay of the excess electron state at a surface trap into the ice layer.…”
Section: Ab Initio Description Of Initial Trapping Sitesmentioning
confidence: 99%
“…Once the excess electron is trapped the dynamical creation of orientational defects or other defects can be envisaged. For example a dynamical reorientation of S 1 -molecules, 10 of S A -molecules (as described above), or of S D such that both D atoms are directed toward the excess electron is conceivable, as the corresponding potential energy surface is quite flat. Such a structural evolution of the defects via conformational substates separated by barriers is thermally activated and hence accelerated at increased temperatures in agreement with the experimental observation (see Figure 6b).…”
Section: Comparison Of Experiments and Theorymentioning
confidence: 99%